Peningkatan Kinerja Karyawan Ditinjau Dari Sikap Kerja Dan Penegakan Keadilan Organisasi - Eli Retnowati; Didit Darmawan (Forum Kerjasama Pendidikan Tinggi, 2022)
Each organization is faced with a reality related to the importance of improving employee performance in an increasingly dynamic organizational environment. This is done as a form of organizational responsiveness in terms of competitive advantage and achieving organizational success. Organizations must be able to examine what factors contribute significantly to making this happen so that a new idea is found. As this study discusses management issues regarding work attitudes, organizational justice, employee performance related to how employee attitudes and organizational justice can play an important role in shaping employee. The respondents are employees of a company located in Gresik City, East Java. In this study the population is all employees with a total of 30 people. The 30 employees are all part of the research sample, so this includes determining the sample using a census technique. The researcher chose the method in two ways, namely observation followed by distributing questionnaires. The analytical tool is used for several stages starting with the classical assumption test, multiple regression analysis, t test and F test. The research data will be processed with the SPSS for windows program where the researcher chooses SPSS version 26. In accordance with the research results obtained, the influence exerted by work attitudes on employee performance is significant. Furthermore, the influence of organizational justice on employee performance also gives similar results, which is significant. Of the two, namely work attitude and organizational justice can affect employee performance simultaneously and significantly.